2012
DOI: 10.9734/bjecc/2012/1475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Awareness and Adaptation to Climate Change among Farmers in the Sahel Savannah Agro-ecological Zone of Borno State, Nigeria

Abstract: This work was carried out as a collaborative effort among all the authors. YLI conceptualized the idea of the work, constructed the data collection instrument, analyzed the data and did the first reporting. AAI collected the data. DBB handled the data entry and assisted in the review. BOO provided the technical know-how, vetted the article and certified it for publication. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 11 publications
(5 reference statements)
9
20
3
Order By: Relevance
“…This implies that majority of the respondents noticed in one way or the other changes in the climatic variables which affect their agricultural activities. This finding concurred with the earlier studies by Idrisa et al (2012); Adebayo et al (2012) who observed that about 82% and 96% of farmers in the Sahel Savanna of Borno State and Adamawa State, Nigeria are aware of climate change respectively. Farmer's awareness of changes in climatic factors (temperature, precipitation, humidity) over time is important for adaptation decision making.…”
Section: Awareness Of Climate Changesupporting
confidence: 91%
“…This implies that majority of the respondents noticed in one way or the other changes in the climatic variables which affect their agricultural activities. This finding concurred with the earlier studies by Idrisa et al (2012); Adebayo et al (2012) who observed that about 82% and 96% of farmers in the Sahel Savanna of Borno State and Adamawa State, Nigeria are aware of climate change respectively. Farmer's awareness of changes in climatic factors (temperature, precipitation, humidity) over time is important for adaptation decision making.…”
Section: Awareness Of Climate Changesupporting
confidence: 91%
“…This probably suggests low knowledge about the adaptation measure. This contradicts the study by Idrisa et al (2012) which shows 80% of the respondents practicing mulching as an adaptation measure to climate change. …”
Section: Coping Strategies Adopted By Farming Households On Climate Ccontrasting
confidence: 57%
“…Further logistic regression analysis finds gender, years of education, and income as significant predictors of the awareness of the importance of climate change. Idrisa et al (2012) examined the awareness and adaptation to climate change among farmers in the Sahel Savannah agro-ecological zone of Borno State, Nigeria found majority of the respondents being aware of climate change from information sources such as agricultural extension services and through friends and relatives. They study therefore recommended that extension education should be strengthened to boost farmers' awareness of climate change and prepare them for adaptation measures and that appropriate/indigenous technologies be promoted for adaptation by farmers.…”
Section: Effect Of Climate Change On Crop Yields In Nigeriamentioning
confidence: 99%